Time in Philosophy, Art and Poetry - Abdullah , Dilkhaz; Juma, Mohammed (Humanities Journal of University of Zakho, 2022)
This research came about the concept of time in the poetic text, to show the great role that time plays in human life from various aspects in philosophy, language, art and poetry, and this is what made the title of the study (time in philosophy, art and poetry), and time has great importance in poetic texts. whose aesthetic value is measured by the extent to which it deals with the issue of time, and this study aims to attempt to shed light on the concept of time in philosophy, art and poetry, so that it appears clearly in this study that time is a tool for language, and that it is one of the most complex linguistic phenomena and the most intractable and indefinitely limited and limited , and that time in the terminology revolves around the era that passes over the life of things and changes occur during it, while it is clear that time in philosophy is a measure of a mathematical quantity, it is that fluid, gelatinous entity that man has known through multiple and different descriptions, while time in art constitutes an avenue. It is difficult to refrain from modern researchers. For the artist, time is a practical practice and not a theory. As for time in poetry, it is the main driver that creates the material of poetry, and that the relationship of poetry with time is a relationship It is a profound one that reaches the point of complete identification between the poet’s inner world and the outside world, and through the above we conclude that the concept of time has a deep and high place in philosophical and human studies since the emergence of linguistic studies, and time is one of the most important pillars on which philosophy relied. A person to do it truly is to give a great value to time while working to produce an art of arts.